Performance optimization of a new combined power cycle based on power density analysis of the dual cycle - Sahin, B; Kesgin, U; Kodal, A; Vardar, N (PERGAMON-ELSEVIER SCIENCE LTD, 2002)
In this paper, maximum power density (MPD) analysis of an air standard internal combustion Dual cycle has been performed. Based on the obtained results for MPD analysis of the Dual cycle, a new combined power cycle model (Dual + Joule-Brayton) has been introduced and optimized. Optimal performance and design parameters are obtained analytically under the MPD conditions of the Dual cycle. The obtained results are discussed in terms of thermal efficiency, power and engine sizes. It is shown that for the combined cycle, a design based on the MPD conditions is more advantageous from the point of view of engine sizes and thermal efficiency. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: maximum power density; performance optimization; dual cycle; Joule-Brayton cycle; combined cycle; ENTROPY GENERATION MINIMIZATION; JOULE-BRAYTON ENGINE; ENDOREVERSIBLE OTTO; DIESEL CYCLE; HEAT ENGINE; MAXIMUM; EFFICIENCY; COMBUSTION; OUTPUT; Thermodynamics; Energy & Fuels; Mechanics